Parenting Style in Instilling Islamic Morals in Early Childhood to Minimize the Negative Influence of the Digital Era - Masrizal, Masrizal (Institut Agama Islam Al-Aziziyah Samalanga, 2025)
The digital era brings easy access to information as well as a serious challenge for the formation of early childhood morals. The rapid development of technology makes children vulnerable to negative influences, both from age-inappropriate content and behaviors formed through digital interactions. This study aims to examine Islamic parenting strategies that can minimize the adverse impact of the digital era on early childhood morals while utilizing it for positive character development. The research method used is library research by examining academic literature such as books, scientific journals, and relevant articles that discuss Islamic parenting, moral development, and digitalization challenges. The analysis was carried out thematically to identify effective and applicable parenting strategies. The results of the study show that a combination of active supervision, habituation of moral values, warm communication, and parental example are the key in forming a children's moral filter. The positive use of technology, such as Islamic educational applications and moral content, can transform gadgets from a threat to an educational tool. In conclusion, adaptive Islamic parenting can be a relevant and sustainable solution in fostering children's morals in the midst of rapid digital currents. This research contributes to strengthening the concept of Islamic parenting based on digital literacy which can be a practical guide for Muslim families.